Glass transition temperature of PMMA/modified alumina nanocomposite: molecular dynamic study. (19th December 2018) - Mohammadi, Maryam; Davoodi, Jamal; Javanbakht, Mahdi; Rezaei, Hamidreza
Abstract: In this study, the effect of alumina and modified alumina nanoparticles in a PMMA/alumina nanocomposite was investigated. To attain this goal, the glass transition behavior of poly methyl methacrylate (PMMA), PMMA/alumina and PMMA/functionalized alumina nanocomposites were investigated by molecular dynamic simulations (MD). All the MD simulations were performed using the Materials Studio 6.0 software package of Accelrys. To obtain the glass transition temperature, the variation of density versus temperature was obtained. The temperature at which the slope of the density-temperature curve observably changes is defined as the glass transition temperature (Tg ). The effect of alumina nanoparticles on the Tg was related to the free volume and the mobility of chain segments and the interaction between the alumina nanoparticles and the polymer. The mobility of the chain segments was investigated based on the mean square displacement and radius gyration. The results show that the incensement the Tg of the PMMA/functionalized alumina nanocomposite is more than that of the PMMA/alumina nanocomposite due to the modification of the alumina nanoparticles.